Undang-Undang Perkawinan dan Kesetaraan Gender: Praktik Relasi Suami-Istri di Kalangan Politikus Perempuan Nahdliyyin - Salmaa Al Zahra Ramadhani (Lakpesdam PCNU Kota Salatiga, 2024)
The background of this research is the changing role of women who are increasingly active in the public sphere, including as legislative members, which affects the construction of relationships in the household. This research aims to analyse husband-wife relations in the families of female DPRD members from the perspectives of gender, Islamic Family Law, and the Marriage Law.The approach used is qualitative with a case study method of four female DPRD members in Semarang Regency. The results showed that there are three patterns of husband-wife relationships, namely husband dominance, wife dominance, and cooperation. These three patterns reflect the complex and diverse dynamics of domestic and public roles, depending on the couple's cultural background, education, and economic conditions. The concept of qiwamah is not always interpreted as absolute male dominance, but rather as a responsibility that can be negotiated according to context. Meanwhile, in Marriage Law Number 1 Year 1974, the husband is referred to as the head of the family and the wife as a housewife. However, practice in the field shows that the division of roles no longer fully follows this construction. This research emphasises the importance of contextual interpretation of religious norms and positive laws in order to create more equal and harmonious household relations. The mubadalah approach is a conceptual offer to build gender-equitable households.